Human impacts and the loss of Neotropical freshwater fish diversity - Pelicice,Fernando M. (2021)
Abstract Neotropical Ichthyology promotes the Special Issue (SI) “Human impacts and the loss of Neotropical freshwater fish diversity” with the purpose of publishing relevant scientific articles on the current biodiversity crisis and the loss of Neotropical freshwater fishes in the Anthropocene. The SI is composed of 22 publications, being two review articles and 20 original articles. A total of 107 researchers contributed to these papers, involving 44 institutions based in Brazil and six other countries. Published articles investigated main anthropic activities and their impacts on fish diversity, with special focus on river regulation, mining, land use changes, aquaculture, and fisheries. Studies provided evidence about the loss of fish diversity in the Neotropics, including fish kill events, demographic changes, contamination, changes in assemblage structure, loss of taxonomic and functional diversity, besides the degradation of ecosystem functions and services, and the lack of effective protection and conservation. Studies were conducted in rivers, streams, lakes, and reservoirs from different Neotropical systems. The studies published in this SI represent a relevant sample of the current worrisome situation of freshwater fishes in the Neotropical region and call for urgent revision in environmental policies, management and conservation initiatives, and socioeconomic priorities.